2005
DOI: 10.1002/ijc.21009
|View full text |Cite
|
Sign up to set email alerts
|

Penile cancer: Importance of circumcision, human papillomavirus and smoking in in situ and invasive disease

Abstract: Few population-based case-control studies have assessed etiologic factors for penile cancer. Past infection with high-risk human papillomavirus (HPV) is a known risk factor for penile cancer; however, few previous studies have related the HPV DNA status of the tumor to potential demographic and behavioral risk factors for the disease or evaluated whether in situ and invasive penile cancer share risk factors. Little information is available on the role and timing of circumcision in the etiology of penile cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
333
5
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(356 citation statements)
references
References 19 publications
15
333
5
3
Order By: Relevance
“…These factors have also been identified in other studies [27][28][29][30], among which people cited as main risk factors the presence of phimosis, low socioeconomic conditions, large number of sexual partners, history of sexually transmitted disease, especially HPV, poor hygiene, smoking, inflammation, and presence of sores or ulcerations in the penis.…”
Section: Discussionsupporting
confidence: 52%
“…These factors have also been identified in other studies [27][28][29][30], among which people cited as main risk factors the presence of phimosis, low socioeconomic conditions, large number of sexual partners, history of sexually transmitted disease, especially HPV, poor hygiene, smoking, inflammation, and presence of sores or ulcerations in the penis.…”
Section: Discussionsupporting
confidence: 52%
“…Systematic reviews show that circumcised men are at significantly lower risk of syphilis and chancroid. 8,9 Circumcised men in the United States are also at significantly lower risk of invasive penile cancer, [10][11][12][13] and a lower risk of cervical cancer in partners of circumcised men has also been reported. 14 This may be due to decreased human papillomavirus infection, which causes ano-genital and cervical cancer.…”
Section: Non-hiv-related Benefits To Women Of Male Circumcisionmentioning
confidence: 99%
“…11 The prevalence of HPV-related high-grade penile intraepithelial neoplasia, however, is very low suggesting that penile tissue is less prone to maintain persistent infection and to undergo neoplastic transformation. As for the cervical cancer pathogenesis, several additional risk factors have been reported, in conjunction with HPV infection, for the development of invasive penile cancer: (i) exogenous cofactors (lack of circumcision in childhood, phimosis, smoking, trauma), 12,13 (ii) host cofactors (genetic factors, immune response) 14,15 and (iii) viral cofactors (infection by specific types, viral load, viral integration status).The frequency of HPV DNA in penile carcinomas greatly vary depending on the tumor histology, the type of analyzed tissue (fresh frozen biopsies versus paraffin-embedded archival samples), virus detection methods and geographical origin. [15][16][17][18][19][20][21][22][23][24][25][26][27] HPV16 is the most prevalent type in penile carcinoma and cervical carcinoma worldwide, with exception of the study by Senba et al, which found HPV18 in 55.4% of the tumors from northern Thailand.…”
mentioning
confidence: 99%